An analysis of airflow patterns in auxiliary ventilated drivages - Moloney, Kenneth W. (1997)
In recent years the drivage advance rates achieved within the UK coal industry have increased. In the 1980's average drivage rates were 35m per week compared to the 100/150m per week possible today. These extended rates of advance have resulted in an increase in the potential methane, dust and heat generation within the vicinity of the drivage face. In order to effectively disperse this additional pollutant load a controlled increase in air quantity is required.